Answer:
Answer
Step-by-step explanation:
The inverse of an exponential function is a logarithmic function and the inverse of a logarithmic function is an exponential function. Notice also on the graph that as x gets larger and larger, the function value of f(x) is increasing more and more dramatically. The inverse of the exponential function y = ax is x = ay. The logarithmic function y = logax is defined to be equivalent to the exponential equation x = ay. y = logax only under the following conditions: x = ay, a > 0, and a≠1.